Assessment of dd-cfDNA Levels in Clinically Stable Lung Allograft Recipients Beyond the Initial 2 y Posttransplant. Issue 12 (17th November 2022) - Trindade, Anil J.; Chapin, Kaitlyn C.; Mullican, Amy; Gray, Jennifer N.; Hoy, Haley; Demarest, Caitlin T.; Lambright, Eric S.; McPherson, Katie A.; Norfolk, Stephanie G.; Robbins, Ivan M.; Bacchetta, Matthew; Erasmus, David B.; et al.
Abstract : Background: Donor-derived cell-free DNA (dd-cfDNA) is a useful biomarker for the diagnosis of acute allograft injury within the first 1 to 2 y after lung transplant, but its utility for diagnosing chronic lung allograft dysfunction (CLAD) has not yet been studied. Understanding baseline dd-cfDNA kinetics beyond the initial 2 y posttransplant is a necessary first step in determining the utility of dd-cfDNA as a CLAD biomarker. We seek to establish baseline dd-cfDNA% levels in clinically stable lung allograft recipients who are >2 y posttransplant. Methods: We performed a prospective, single-center, observational study to identify plasma dd-cfDNA levels in clinically stable lung allograft recipients >2 y posttransplant. Results: Fifty-one subjects were enrolled and ≥3 baseline dd-cfDNA measurements were acquired during a median of 252 d. The median baseline percent dd-cfDNA level in our cohort was 0.45% (interquartile range [IQR], 0.26–0.69). There were statistically significant differences in dd-cfDNA based on posttransplant duration (≤5 y posttransplant median 0.41% [IQR, 0.21–0.64] versus >5 y posttransplant median 0.50% [IQR, 0.33–0.76]; P  < 0.02). However, the clinical significance of this small change in dd-cfDNA is uncertain because this magnitude of change is within the biologic test variation of 73%. Conclusions: This study is the first to define levels of dd-cfDNA in clinically stable patients who are >2 y post–lung transplant. These findings lay the groundwork for the study of dd-cfDNA as a possible biomarker for CLAD. Abstract :